Positive and Negative Affect as Mediator of the Relatioship Optimism-Health: Evaluation of a Structural Model - Vera-Villarroel, P; Celis-Atenas, K (PONTIFICA UNIV JAVERIANA, FAC PSYCH, 2014)
Psychological variables and especially the positive variables have shown multiple benefits for humans. Important evidence indicates that subjects with better well-being higher levels of happiness and positive emotions show better health indicators. Optimism is a positive variable widely studied and strong evidence of its benefits on the health of individuals. However, an explanatory model about how these benefits occur has been less studied. It has been proposed to evaluate a model that establishes optimism can be a causal variable health mediated the positive and negative affects. An analysis of structural equation modeling was conducted to test an explanatory model. Participants 995 people aged between 18 and 60 years old. Dispositional optimism, positive and negative affect as well as mental and physical health was assessed. Structural model analysis was conducted to test an explanatory model. The results show that the model is suitable adjustment to consider allowing optimism as an explanatory variable of both physical and mental health mediated by positive and negative affect.